EFFECT OF ISO 17025 STANDARD ON QUALITY MANAGEMENT SYSTEM IN ACCREDITED CIVIL ENGINEERING LABORATORIES - CEYLAN , Melek; CANSIZ , Sinan (SSD Journal, 2022)
Due to the earthquakes that have occurred in recent years, many lives and property have been lost in the world. After these earthquakes, national and international regulations used in the world have updated with various changes. Especially the regions where the population and industry in Turkey are dense are under the risk of heavy earthquakes. When the damages in the buildings after the earthquakes were examined, it has seen that they are in poor quality and uncontrolled structures. The inspection of the buildings has built in Turkey is carried out by the relevant municipalities and ministries. The most important part of these inspections is carried out by laboratories that inspect the suitability of the materials used. The importance of public and private control laboratories in the field of construction organized under the ISO/IEC 17025 standard in Turkey is important for the safety of buildings. In this context, the effectiveness of the construction materials laboratories in Turkey according to the ISO 17025 standard has investigated. In this context, the establishment processes of the civil engineering laboratory, which is in the process of establishment and for which an accreditation application will be made, have examined in accordance with the ISO 17025 standard. In addition, the compliance of the laboratory's quality management system documents with the ISO 17025 standard has investigated. Thanks to this study, it is aimed to assist the accreditation processes of organizations that want to be accredited.